Price Coordination with Asymmetric Information Sharing: Theory and Evidence - Byrne, David P.; de Roos, Nicolas; Lewis, Matthew S.; Marx, Leslie M.; Wu, Xiaosong (The Review of Economics and Statistics, 2025)
Abstract Platform-based information sharing among competing firms presents challenges for antitrust authorities, yet effective remedies remain unclear. Drawing inspiration from the Informed Sources retail gasoline antitrust case, we develop a theoretical model that offers policy guidance for disrupting anticompetitive coordination facilitated through price-sharing platforms. Removing only one firm from a platform may be ineffective for disrupting such coordination. However, competitive benefits can emerge if (i) at least two firms lack platform access, and (ii) the costs of price leadership are sufficiently high. More broadly, coordinating price increases becomes more difficult when multiple firms cannot quickly observe or respond to rivals' prices.